Zhike Pingchuan Granule suppresses interleukin (IL)-6 or the medium of M2 macrophages induced apoptosis in human bronchial epithelial cells. Issue 1 (1st January 2021) - Ren, Yumei; Yan, Yongbin; Zhen, Lei; Cao, Caihong; Wang, Quan; Zhang, Yingying; Zhu, Shan
ABSTRACT: The aim of this study was to explore the effects and action mechanism of Zhike Pingchuan Granule in human bronchial epithelial cells induced by IL-6 or the supernatant of M2. Upon IL-6 stimulation at different doses, Cell Counting Kit-8 (CCK8) assay and flow cytometry were, respectively, utilized to detect the cell viability and apoptosis levels of 16-HBE cells. ELISA and Western blot were, respectively, used to analyze the inflammatory markers and JAK2/STAT3 signals. Immunofluorescence assay was performed to identify M0 and M2 cells. As shown in results, ZKPC perturbed the expression of IL-6 inducible genes important for apoptosis, oxidative and inflammatory response, which was enhanced by JAK2 inhibitor. Besides the inhibitory effects on the phosphorylation levels of JAK2/STAT3, ZKPC markedly increased cell viability and reduced apoptosis in human bronchial epithelial cells (16-HBE) cultured in the supernatant of M2 cells. Collectively, ZKPC could inhibit the IL-6-induced JAK/STAT3 signaling cascade, increase cell viability and decrease apoptosis induced by the supernatant of M2. A more comprehensive understanding of the action mechanism of ZKPC on JAK2/STAT3 signaling pathway in human bronchial epithelial cells induced by IL-6 or M2 supernatant will enable ZKPC development in the control of asthma.